Darwin customizable resource management for value-added network services. - Chandra, P. (IEEE Network : the magazine of global information exchange)
The Internet is rapidly changing from a set of wires and switches that carry packets into a sophisticated infrastructure that delivers a set of complex value-added services to end users. Services can range from bit transport all the way up to distributed value-added services like video teleconferencing, virtual private networking, data mining, and distributed interactive simulations. Before such services can be supported in a general and dynamic manner, we have to develop appropriate resource management mechanisms. These resource management mechanisms must make it possible to identify and allocate resources that meet service or application requirements, support both isolation and controlled dynamic sharing of resources across services and applications sharing physical resources, and be customizable so services and applications can tailor resource usage to optimize their performance. The Darwin project has developed a set of customizable resource management mechanisms that support value-added services. We present and motivate these mechanisms, describe their implementation in a prototype system, and describe the results of a series of proof-of-concept experiments